Services in the European Union : what kinds of regulatory policies enhance productivity? - van der Marel, Erik; Kren, Janez; Iootty, Mariana (Washington, DC, 2017)
"This paper is the first one to show the effects of services regulations on downstream firms in the goods and services sectors in a multiple-country setting using firm-level data. The study selected a group of countries that are economically relatively services-oriented and show varying degrees of services regulations over time, namely the European Union. The paper employs four alternative firm-level measures of total factor productivity that have recently been developed in the economics literature and provide robust conclusions. Overall, the results suggest that regulatory barriers in services have diverse effects on downstream manufacturing performance, depending on the type of regulatory measure in question. The policy variables are split into pure entry barriers and those that relate to the anti-competitive policies on the operations of the firm, which the paper calls conduct regulations. The latter appear to play the most important role in explaining downstream performance across services and goods firms. Furthermore, the results show that regulations matter significantly more in the cases when a country is institutionally weak, an industry is considered as relatively close to the technology frontier, or a firm is foreign owned."